2018
DOI: 10.1080/09540121.2018.1499864
|View full text |Cite
|
Sign up to set email alerts
|

Persistent stigmatizing and negative perceptions of pre-exposure prophylaxis (PrEP) users: implications for PrEP adoption among Latino men who have sex with men

Abstract: The Centers for Disease Control and Prevention (CDC) estimates the lifetime HIV risk is one in four for Latino men who have sex with men (MSM). Pre-Exposure Prophylaxis (PrEP) is an efficacious biomedical prevention strategy to help prevent the acquisition of HIV. At present, there has been limited uptake of PrEP by Latino MSM. Unfortunately, the negative perceptions and social stigma surrounding PrEP and those who use it may deter uptake of this novel prevention strategy, particularly among high-risk Latino M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…As the current COVID-19 pandemic shows, mHealth technologies can provide a crucial link to relay quickly evolving information. Recent studies [10][11][12][13][14][15] including our own [8,16,17] have shown how increasingly restrictive U.S. immigration policies [18] have heightened the unwillingness of many LSMM and LTGW to engage with formal systems, [19] further elevating the need to utilize mHealth platforms to maintain a critical line of communication. MHealth shows potential to improve HIV testing frequency among these groups, [20][21][22][23][24][25] but evidence of technology disengagement over time [26] makes it unclear how best to achieve this outcome [9,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…As the current COVID-19 pandemic shows, mHealth technologies can provide a crucial link to relay quickly evolving information. Recent studies [10][11][12][13][14][15] including our own [8,16,17] have shown how increasingly restrictive U.S. immigration policies [18] have heightened the unwillingness of many LSMM and LTGW to engage with formal systems, [19] further elevating the need to utilize mHealth platforms to maintain a critical line of communication. MHealth shows potential to improve HIV testing frequency among these groups, [20][21][22][23][24][25] but evidence of technology disengagement over time [26] makes it unclear how best to achieve this outcome [9,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Another consequence of using PrEP identified in this study was the conflict it introduced in relationships, which often centered on questions or concerns regarding trust, potential infidelity, and monogamy. In general, PrEP is considered a necessary and acceptable form of HIV prevention for persons in HIV serodiscordant relationships [33]. It is primarily within the context of HIVnegative seroconcordant relationships that conflicts arise, wherein the use of PrEP by one partner is perceived as an indication of their infidelity or lack of trust in the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Social barriers comprise factors related to negative community perceptions of PrEP users, such as assumptions made about their promiscuity or HIV status [17,40]. Similar to other researchers, we suggest that PrEP navigators or peer educators may help bridge the current gap between high awareness and acceptability and low uptake of PrEP among Latino MSM and recommend that navigators or peer educators be other Latino MSM [11,[40][41][42][43]. We also suggest that PrEP delivery occur in safe spaces, such as community-based organizations that have earned the trust of Latino MSM.…”
Section: Discussionmentioning
confidence: 99%